2022
DOI: 10.1002/ehf2.13886
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of nutritional indicators in patients with heart failure

Abstract: Aims The aim of this study was to compare the diagnostic performance of the nutritional indicators, the mini nutritional assessment‐short form (MNA‐SF), the geriatric nutritional risk index (GNRI), and the controlling nutritional status (CONUT), in heart failure (HF) patients. Methods and results Nutritional status was prospectively assessed by the aforementioned three nutritional indicators in 150 outpatients with HF who were then followed for 1 year. The prevalence of patients with the nutritional risk as as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Second, some of the patients with HF were treated with statins, which can influence the cholesterol levels. A recent study suggests that statin use affects the efficacy of CONUT, 40 but previous findings are inconsistent. The results of the present study suggest that the effect of statins on CONUT was less, probably because statins were used in similar proportions in all groups in relation to the indications of patients with ischaemic heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Second, some of the patients with HF were treated with statins, which can influence the cholesterol levels. A recent study suggests that statin use affects the efficacy of CONUT, 40 but previous findings are inconsistent. The results of the present study suggest that the effect of statins on CONUT was less, probably because statins were used in similar proportions in all groups in relation to the indications of patients with ischaemic heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cut-point for malnutrition by the PNI was inconsistent in different studies, which would hamper its wildly clinical use ( 48 ). It had been cautious that the total cholesterol level was included as a component in calculating the CONUT score, which would overestimate the prevalence of malnutrition in patients with HF, as most of them may receive statins treatment and resulted in a lower total cholesterol level ( 5 ). In the same cohort of patients, it had been shown that the prevalence of malnutrition would be up to 54% when defined by the CONUT, while only 8% when defined by the PNI ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Early detection of malnutrition in HF would be useful for identifying patients at high risk of poor clinical outcomes and recommending nutritional interventions to improve prognosis (7). Many tools and indexes had been proposed for screening malnutrition; however, no consensus had been made on which to use in patients with HF (5,(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacotherapy is recommended as the first line therapy on CHF (8,9). But in recent years, some researchers have focused on factors other than pharmacotherapy, for instance nutrition and infection (10)(11)(12). For patients with CHF, Gastrointestinal edema caused by fluid retention often leads to in appetence, and energy intake reduction over a long period of time leads to malnutrition.…”
Section: Introductionmentioning
confidence: 99%